Polymicrobial Pituitary Abscess Predominately Involving Escherichia coli in the Setting of an Apoplectic Pituitary Prolactinoma - Norman Beatty; Luis Medina-Garcia; Mayar Al Mohajer; Tirdad T. Zangeneh (Case Reports in Infectious Diseases)
Pituitary abscess is a rare intracranial infection that can be life-threatening if not appropriately diagnosed and treated upon presentation. The most common presenting symptoms include headache, anterior pituitary hypofunction, and visual field disturbances. Brain imaging with either computed tomography or magnetic resonance imaging usually reveals intra- or suprasellar lesion(s). Diagnosis is typically confirmed intra- or postoperatively when pathological analysis is done. Clinicians should immediately start empiric antibiotics and request a neurosurgical consult when pituitary abscess is suspected. Escherichia coli (E. coli) causing intracranial infections are not well understood and are uncommon in adults. We present an interesting case of an immunocompetent male with a history of hypogonadism presenting with worsening headache and acute right eye vision loss. He was found to have a polymicrobial pituitary abscess predominantly involving E.   coli in addition to Actinomyces odontolyticus and Prevotella melaninogenica in the setting of an apoplectic pituitary prolactinoma. The definitive etiology of this infection was not determined but an odontogenic process was suspected. A chronic third molar eruption and impaction in close proximity to the pituitary gland likely led to contiguous spread of opportunistic oral microorganisms allowing for a polymicrobial pituitary abscess formation.